The flexural behavior of composite sandwich structure - Mohd Hakim, Omar (2008)
Sandwich construction is widely used because of its ability to provide high bending stiffness coupled with light weight. The main objective of this study is to investigate the effects of core under flexural test and to investigate performance of sandwich panels from the energy absorption point of view. The fibre used is woven roving glass fibre where the matrix used is based on saturated polyester resin. The composite skins of the sandwich panels were prepared by hand lay-up technique. Three point bending test was carried out to obtain flexural strength and flexural strain of the composite sandwich structures. Two different cores of sandwich panels were tested in this project. Sandwich panels with polyurethane core was found had higher flexural strength and higher energy absorption compared with sandwich panels with polyethylene core. From the observation, increasing the debonding strength of the core-face interface, the failure mode changed from debonding of the core-face interface to the failure of the face. The experimental results show that mechanical properties were improved when span decreased and also depends on core materials. Thus, the influence of core materials and span length of the sandwich panels has been evaluated.